(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The occurrence of gastrointestinal helminths was investigated in 50 house rats (Rattus rattus) trapped from two habitats; domestic area and paddy field area of Dhaka, Bangladesh during May 2014 to April 2015. The prevalence of helminths was 88% (44/50) and intensity was 34.73 (1528 parasites from 44 hosts). The study revealed that the rodents were infected with eight species of parasites (one trematode, four cestodes and three nematodes) which were collected from gastrointestinal tract and liver of the hosts. Of the helminths, the dominant parasites were Echinostoma cinetorchis (36.52%) followed by Heterakis spumosa (31.74%), Hymenolepis nana (7.26%), Syphacia obvelata (7.13%), Hydatigera taeniaeformis (6.68%), Oesophagostomum eurycephalum (5.04%), Hymenolepis diminuta (3.01%) and Hymenolepis sp. (2.62%). Domestic rats showed the highest prevalence of infestation (90%) compared to paddy field rats (85%), whereas the intensity was lower (30.30 ± 10.53) in domestic rats than in the paddy field rats (41.77 ± 12.79). Peak prevalence was observed in males but intensity was found higher in female host. Occurrence of double infection was higher in domestic rats (53.33%). Intestine was the favorite niche compared to other organs. The highest prevalence was observed in winter and spring and the intensity was the highest in autumn in domestic rat, whereas in paddy field rat, the highest prevalence was observed in autumn and spring, the intensity was also the highest in spring. In both the hosts, intermediate length groups and highest weight groups were more vulnerable to infection. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 74-79